1999
DOI: 10.1086/314823
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cytokine Mediation of Disease Expression in Adults Experimentally Infected with Influenza A Virus

Abstract: The roles of interleukin (IL)-6 and IL-8 in mediating the symptoms and signs of influenza A infection were examined. Adults were intranasally inoculated with a rimantadine-sensitive strain of influenza A HlNl virus and treated with rimantadine or placebo. Viral shedding, secretion weights, symptom scores, and concentrations of IL-6 and IL-8 in nasal lavage fluids were compared between treatment groups. Viral shedding was associated with increases in local and systemic symptoms, in expelled secretion weights, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 26 publications
3
97
2
Order By: Relevance
“…However, there is still uncertainty regarding the implications of cytokines in symptoms of common cold. For example, while some studies demonstrate an increase in IL-8 during early infection, other studies have shown to peak around day 4-6 (Hayden et al, 1998;Skoner et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still uncertainty regarding the implications of cytokines in symptoms of common cold. For example, while some studies demonstrate an increase in IL-8 during early infection, other studies have shown to peak around day 4-6 (Hayden et al, 1998;Skoner et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…27 A wide range of cytokines and chemokines are produced in the human upper and lower respiratory tract in response to influenza infection, including interleukin-6 (IL-6), IL-8, IL-10, tumor necrosis factor-␣ (TNF-␣), interferon-␣, interferon-␥, macrophage inhibitory protein-␣, macrophage inhibitory protein-1␤, and macrophage chemotactic protein-1. [28][29][30][31] Moreover, the proinflammatory cytokines, IL-6 and TNF-␣, are found in serum and plasma after experimental influenza infection in humans. 31 Therefore, circulating cytokines and chemokines, together with bacterial endotoxin, may contribute to hepatic damage in the absence of hepatic seeding of the virus.…”
Section: Mechanism Of Hepatic Damagementioning
confidence: 99%
“…Levels of IL-8 and IL-6 are increased in airway secretions from individuals with respiratory viral infection (14,18,31). Furthermore, the kinetics and magnitude of IL-8 and IL-6 production correlate with respiratory symptoms in influenza infection (18,31), thus underlining the prominent role of these mediators in virus-induced pathophysiology.…”
mentioning
confidence: 96%